HUBUNGAN ANTARA KEPEMIMPINAN, PELATIHAN, REWARD, DAN PUNISHMENT TERHADAP KINERJA KARYAWAN IIB DARMAJAYA - Asnusa, Soraya; Aziz, RZ Abdul (Jurnal Manajemen Magister Darmajaya, 2018)
IIB Darmajaya is one of the private universities in Lampung province. IBI Darmajaya has become the technologyand business-based university and dominated the marketplace in Bandar Lampung. The problem statement of this research was that the employee performance in IBI Darmajaya was not optimum. The variablesof this research were the leadership, training, reward, and punishment. The objective of this research was to determine the leadership, training, reward and punishment on the employee performance so that the researcher needed to know to what extent the correlation of the leadership, training, reward and punishment on the employeeperformance. The sampling technique used in this research was non-random sampling technique. The population of this research was 215 employees. The sample used in this research was 68 employees. The data collecting technique used in this research was questionnaire. The results of this research showedwas that the leadership, training, reward and punishment were the most important variables to improve the employee performance because all of these variables had a significant effect.Keywords : Leadership, Training, Reward, Punishment and Performance